Who am I today? Professional Transformation Resulting from Reflections on Working with Mothers - Jiménez-Salas, Evelyn (2015)
The article presents my personal story during my time in higher education and some of the experiences and ideas that marked my preparation as an Occupational Therapist, as well as my construction and reconstruction during my time in the Graduate Program in Pedagogy at the National University (Costa Rica); which resulted in my own transformation that I experienced along with the subjects of a participatory action research process and the theoretical references that framed this experience.  It is vital to contextualize this article because it is only knowing and decomposing the structure of the language from which it was written that the reader will be able to discover the different meanings in these words.  This article describes the paradigm shift that I experienced while working as an Occupational Therapist and being an active participant in an action research process with a group of 15 families, mostly represented by mothers with a child with special educational needs in the process of being transferred to another educational center.  The research project implied working jointly, blending the experiences and knowledge of those mothers who have already been through the transfer, with the experiences of those mothers about to do it, in addition to those of the researcher.  It was clear from the beginning that these conditions are crucial but are not the only ones that play a role in our Special Education Center.  An important part of the process was the possibility to see ourselves reflected on each other’s experiences, which helped validate feelings and ways of processing and solving problems, as a result of exposing ourselves to everyday demands.